Pharmacological and Chemical Study to Identify Wound-Healing Active Compounds in Ageratina pichinchensis - Romero-Cerecero, Ofelia; Zamilpa, Alejandro; González-Cortazar, Manasés; Alonso-Cortés, Daniel; Jiménez-Ferrer, Enrique; Nicasio-Torres, Pilar; Aguilar-Santamaría, Lucía; Tortoriello, Jaime (Planta Medica, 2013)
The aerial parts of Ageratina pichinchensis are used in Mexican traditional medicine for the treatment of skin wounds. Recently, it was demonstrated that the aqueous extract of this plant reduced the time required to cicatrize a wound induced in the rat. The same extract showed a capability to induce overgrowth in normal fetal lung cells (MRC-5). The objective of the present study was isolating and identifying the active compounds in A. pichinchensis that are capable of inducing cellular overgrowth, as well as performing a preliminary evaluation of their anti-inflammatory and toxic effects. By means of bioguided chemical separation of an aqueous extract of A. pichinchensis, the most active compound capable of inducing cellular overgrowth was identified as 7-O-(β-D-glucopyranosyl)-galactin. In vivo inflammation induced with carrageenan in mice was significantly reduced by the aqueous extract of A. pichinchensis, reaching a decrease of up to 60.6 %. Acute (2 g/kg) and subchronic (1 g/kg for 28 days) oral administration of the aqueous extract of this plant did not affect hepatic function (through alanine aminotransferase and aspartate aminotransferase activity evaluation), while no alterations of the histologic samples of liver and kidney were evidenced.
Keywords: Ageratina pichinchensis; Asteraceae; cell overgrowth; wound healing; 7-O-(β-D-glucopyranosyl)-galactin; anti-inflammatory; toxicology